Analytical definition of parameters the drying agent for a real dryer. - M. K. Zaharov; V. V. Karasev (Тонкие химические технологии, 2007)
The method suggested in the article makes it possible to calculate by analytics the parameters of the drying agent at the moment of its going out of the real dryer at the certain terminal (final) air temperature or humidity. The method concerned dives an opportunity to refuse from using I-x diagram